A Three‐Dimensional View on Soil Biogeochemistry: A Dataset for a Forested Headwater Catchment. Issue 1 (1st January 2017) - Gottselig, N.; Wiekenkamp, I.; Weihermüller, L.; Brüggemann, N.; Berns, A. E.; Bogena, H. R.; Borchard, N.; Klumpp, E.; Lücke, A.; Missong, A.; Pütz, T.; Vereecken, H.; et al.
Abstract : Current understanding of the variability in soil properties and their relationship to processes and spatial patterns in forested landscapes is limited due to the scarcity of datasets providing such information. Here we present a spatially highly resolved dataset (http://teodoor.icg.kfa‐juelich.de/ibg3searchportal2/dispatch?metadata.detail.view.id=e3886301‐7252‐4142‐b1a4‐333dfe7f1ca4 ) that provides detailed information on the three‐dimensional variability of biogeochemical properties in the Wüstebach catchment (western Germany), a long‐term environmental observation site of the TERENO (Terrestrial Environmental Observatories) project. High‐resolution soil sampling was conducted, and physical and biogeochemical soil parameters were recorded per horizon. The dataset is helpful in the analysis of the spatial heterogeneity in biogeochemical properties within soil horizons and with depth through the soil profile. In addition, it shows links between hydrological and biogeochemical properties and processes within the system. Overall, the dataset provides a high‐resolution view into (re)cycling, leaching, and storage of nutrients on the catchment scale in a forested headwater catchment. Core Ideas: A dataset with 3‐D views of biogeochemical soil parameters in a forested headwater catchment is described. Dataset provides information on spatial heterogeneity and vertical distribution of nutrients. Transdisciplinary approach: soil chemistry, soil physics, and long‐term monitoring data.